The study of ant colony optimization (ACO) parameters for STATCOM optimization / Melor Md Hodari - Md Hodari, Melor (2010)
Continuous demand in power transmission network caused by reactive power has been highlighted as the main factor in voltage depreciation and also increase of total transmission loss. Past studies have reported several possible techniques such as optimal reactive power dispatch, optimal capacitor placement; transformer tap setting and static VAR compensator are solutions for reducing voltage collapse occurrences. This paper presents Ant Colony Optimization (ACO) technique to improve voltage stability condition along with transmission loss and voltage profile monitoring using STATCOM. The purpose is to search for a solution for the best parameters of ACO that will improve the voltages and also to reduce the power losses in an electric power system. The proposed technique was tested using the standard IEEE 30-bus system and the capability of developed ACO in solving continuous optimization problems has been revealed as the added value in the algorithm.